Síntese de redes de trocadores de calor flexíveis - Módenes, Aparecido Nivaldo (1995)
In this work a computational program was developed for the synthesis of flexible heat exchanger networks. The program uses the concepts of Pinch Analysis to design project the network to only one operating period (named Base Case) and uses the a flexibility analysis to achieve the final design for all the other periods. In the heat exchanger network synthesis, initially are defined for the Base Case, the objectives with respect the minimum global cost, the optimum DTmin, the minimum exchange area, the minimum number of units and the hot and cold utilities. The network is synthesized by using the Pinch Design Method. After this, the network is evolved, identifying and breaking loops. After the evolution, it is made the flexibility analysis. This analysis has as objective to adapt the Base Case to the others periods with a fewer global cost, getting the trade-off between the capital and the energy cost to the final network, for all the periods of operation. Some examples of the literature were used to test and compare the results, showing the developed technique consistence and its applicability.